Terapi Bermain Untuk Meningkatkan Kekuatan Motorik dan Kognitif pada Lansia Binaan Stikes Bala Keselamatan Palu di Kota Palu - Ni Luh Emilia; Denny Susanto; Meilin Anggreyni; Juliana Neng Rifka Sarman (PT.Mantaya Idea Batara, 2022)
The age group with the fastest growth in the world today is elderly. The health problems experienced by the elderly are varied, such as cognitive disorders and physical or motor problems. Various efforts have been made to restore this condition, one of them is play therapy. The purpose of this community service is to provide play therapy to improve motor and cognitive strength to the elderly that are fostered by Stikes Bala Keselamatan Palu which is located in Palu City. The method in this activity was done by interviewing, observing and running a questionnaire to measure cognitive of the elderly using the MMSE (Mini Mental State Examination) questionnaire and to measure the client's motor strength, it was used an assessment of muscle strength then the elderly was divided into several small groups with 5 types of games or activities which will be carried out alternately. The results obtained were that 24 elderly who were willing to take part in play therapy activities with MMSE results data, there were 21 elderly who got an average score of < 21 which means that the elderly have cognitive impairment and the average muscle strength of the elderly has a value of 4 which means there were still lots of elderly who have muscle weakness. After the play therapy was carried out, the elderly seemed active, enthusiastic and very happy with this activity. It is recommended that the health workers, especially community health center, can add this play therapy to the elderly integrated services post program.